Data regulation with Chinese characteristics - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2019)
Data regulation has become a key issue in today’s world. For various reasons, however, it has been challenging to understand data regulations in China, home to the largest e-commerce market in the world. This paper traces the evolution of data and Internet regulation in China, from the early days of the Chinese Internet, to the regulatory turf wars among different agencies, and all the way to the elevation of data and Internet regulation to the level of national security and the rise of a super-agency in charge of the issue in recent years. The paper argues that, the Chinese Internet regulation has evolved from the regulation of the hardware and then software, to the regulation of content and now data. Through a detailed analysis of the rationale and operation of “data regulation with Chinese characteristics”, the paper aims to not only help people understand the inherent logic and mechanisms of the Chinese data regulatory model, but also find ways to deal with such regime at the international level, especially in view of the ongoing Joint Statement Initiative negotiations on electronic commerce.